Heparan sulfate targets the HIV-1 envelope glycoprotein gp120 coreceptor binding site. - Vivès, R; Imberty, A; Sattentau, Q; Lortat-Jacob, H (2005)
Human immunodeficiency virus (HIV) attachment to host cells is a multi-step process that involves interaction of the viral envelope gp120 with the primary receptor CD4 and coreceptors. HIV gp120 also binds to other cell surface components, including heparan sulfate (HS), a sulfated polysaccharide whose wide interactive properties are exploited by many pathogens for attachment and concentration at the cell surface. To analyze the structural features of gp120 binding to HS, we used soluble CD4 to constrain gp120 in a specific conformation. We first found that CD4 induced conformational change of gp120, dramatically increasing binding to HS. We then showed that HS binding interface on gp120 comprised, in addition to the well characterized V3 loop, a CD4-induced epitope. This epitope is efficiently targeted by nanomolar concentrations of size-defined heparin/HS-derived oligosaccharides. Because this domain of the protein also constitutes the binding site for the viral coreceptors, these results support an implication of HS at late stages of the virus-cell attachment process and suggest potential therapeutic applications.